2020
DOI: 10.1016/j.cmi.2020.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole plus terbinafine combination antifungal therapy for invasive Lomentospora prolificans infections: analysis of 41 patients from the FungiScope® registry 2008–2019

Abstract: Clinical Microbiology and Infection 26 (2020) 784.e1e784.e5 Olorofim Outcomes Treatment Terbinafine Scedosporium Voriconazoleantifungal therapy was associated with increased 28-day survival (15/24 survived versus 4/16 receiving monotherapy; p 0.027) and the combination voriconazole plus terbinafine trended to be associated with higher rates of treatment success (10/16, 63%, 95% CI 35%e85%) compared with other antifungal treatment regimens (7/24, 29%, 95% CI 13%e51%, p 0.053). In KaplaneMeier survival analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 16 publications
1
55
1
Order By: Relevance
“…Clinical studies have demonstrated the superiority of voriconazole‐based treatment regimens for L prolificans infections compared to LAmB‐based regimens, a finding that was confirmed in our study. Furthermore, recently published data from our cohort showed the highest treatment success with voriconazole when used in combination with another antifungal agent. Importantly, 39% of patients in our cohort had L prolificans breakthrough infections occurring under triazole prophylaxis/empirical therapy, with more than a third occurring during voriconazole prophylaxis, further evidence that voriconazole alone may be insufficient to prevent or treat infections caused by L prolificans .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Clinical studies have demonstrated the superiority of voriconazole‐based treatment regimens for L prolificans infections compared to LAmB‐based regimens, a finding that was confirmed in our study. Furthermore, recently published data from our cohort showed the highest treatment success with voriconazole when used in combination with another antifungal agent. Importantly, 39% of patients in our cohort had L prolificans breakthrough infections occurring under triazole prophylaxis/empirical therapy, with more than a third occurring during voriconazole prophylaxis, further evidence that voriconazole alone may be insufficient to prevent or treat infections caused by L prolificans .…”
Section: Discussionsupporting
confidence: 54%
“…Only seven patients received voriconazole monotherapy (median 22 days, IQR 3‐47 days); of those, 4/7 (57%) had treatment failure with IFI‐attributed mortality within 28 days of diagnosis, while 3/7 (43%) survived. Better outcomes were observed in those with combination antifungal therapy, and specifically, those receiving voriconazole + terbinafine combination therapy are described in detail elsewhere …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although broad-spectrum antifungal agents have decreased the rates of bIC, breakthrough infection with moulds still occurs despite a variety of antifungal agents. [52][53][54][55] A fumigatus and multi-resistant yeasts have caused bIFI in patients receiving caspofungin, 48,49,56,57 and A fumigatus resistant to azoles has started to emerge in some countries as a product of long-term therapy, or from environmental azole use. 58 Mucormycosis and infections caused by other rare moulds such as Fusarium spp.…”
Section: Fungal Factorsmentioning
confidence: 99%
“…However, more recent studies suggest that combination treatments are associated with improved outcomes in L prolificans infections, particularly when using voriconazole plus terbinafine. 39,40 Therefore, this combination-the first option in our hospital-should currently be the first choice of treatment in Lomentospora-related IFIs, as recommended by Guidelines. 41 Limitations of our study include the retrospective approach and its origin in a single centre.…”
Section: Discussionmentioning
confidence: 99%